Pengaruh Harga dan Kualitas Layanan terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Pengguna Netflix - Sajidah, Nisrins As; Anggarawati, Sularsih (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The aims of the research is to provide knowledge about the relationship between price and service quality on customer loyalty through customer satisfaction among Netflix users. The method used was a purposive sampling method with a sample size of 206 Netflix streaming application users aged 17-25 years who focused on the city of Bengkulu. The research uses SEM with one of the PLS methods using smartpls 4.0 software to get a more detailed understanding of the respondent's perspective. In accordance with the results of statistical tests, price is significantly related to customer satisfaction even though it is low. Service quality is also positively related to customer loyalty, as is customer satisfaction to customer loyalty. For mediation testing using the upsilon v effect method. Price partially mediates customer satisfaction and customer loyalty, but at a structural level the mediating influence is still relatively low. Meanwhile, the mediating influence of service quality fully mediates customer satisfaction and customer loyalty.